Cortical Electrophysiological Markers of Language Abilities in Children with Hearing Aids: A Pilot Study. (19th August 2014) - Bakhos, David; Delage, Hélène; Galvin, John; Lescanne, Emmanuel; Roux, Sylvie; Bonnet-Brilhault, Frédérique; Bruneau, Nicole
Abstract : Objective . To investigate cortical auditory evoked potentials (CAEPs) in pediatric hearing aid (HA) users, with and without language impairment. Design . CAEPs were measured in 11 pediatric HA users (age: 8–12 years) with moderate bilateral sensorineural hearing loss (HL); participants were classified according to language ability. CAEPs were also measured for a control group of 11 age-matched, normal-hearing (NH) children. Results . HL children without language impairment exhibited normal CAEPs. HL children with language impairment exhibited atypical temporal CAEPs, characterized by the absence of N1c; frontocentral responses displayed normal age-related patterns. Conclusion . Results suggest that abnormal temporal brain function may underlie language impairment in pediatric HA users with moderate sensorineural HL.